Mapping the spatial and affective composition of care in a drug consumption room in Germany. (13th June 2021) - Duncan, Tristan; Sebar, Bernadette; Lee, Jessica; Duff, Cameron
ABSTRACT: This paper attends to the activity of care as it is articulated, enacted and contested within a drug consumption room in Germany. Drawing on empirical data generated during a long-term participatory ethnography conducted in Frankfurt, our analysis attends to the 'invisible labors' of care, alongside the more visible practices by which care is enacted and contested. We unsettle depictions of care as innate and unproblematic components of service delivery in consumption rooms by interrogating care's 'fraught politics'. While mapping relations of care woven through the consumption room, we ask, what modes of care are constrained, subjugated, erased, or neglected within these spaces? We also investigate how diverse modalities of care intersect in the consumption room, what experiences of caring are produced amidst these intersections, for whom, and to what effect. Our analysis aims to make the practices, logics, and techniques that constitute care in the consumption room amenable to critical reflection. In so doing, we contribute to recent discussions of the ethics of care, and they ways it might sustain novel modes of social, affective and material care in drug consumption rooms.